Pelatihan permainan hockey outdoor - Syahruddin Syahruddin; M. Syahrul Saleh; Abdul Rahman (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Game Hockey sports consist of several forms of games namely, outdoor hockey, indoor hockey, and hokey ice. Popular hockey in Indonesia, especially on the islands of Java and Kalimantan, is an outdoor hockey with 11 (eleven) players. This game has been played in South Sulawesi since the 1980s. However, hockey experienced a decline both in popularity and in achievement. It can be seen that the game of hockey, has never been competed in the Inter-Regional Sports Week (PORDA) although it is a sport that is competed in the Olympics. The method used is 1) Providing theory and practice of basic technical training individually or in groups, 2) Providing training by providing viewing through picture and video media, 3) Providing training by providing examples and guiding both individually and in groups. In this activity, it was seen that the enthusiasm and interest of students in playing hockey was very good and quite high. Students want this sport to be included in the education curriculum at school, so that it is always to be played and studied further